Detection of abnormal MR brains based on wavelet entropy and feature selection. Issue 3 (10th February 2016) - Zhou, Xing‐Xing; Zhang, Yudong; Ji, Genlin; Yang, Jiquan; Dong, Zhengchao; Wang, Shuihua; Zhang, Guangshuai; Phillips, Preetha
Abstract : An accurate diagnosis is important for the medical treatment of patients suffering from brain diseases. Magnetic resonance (MR) images are commonly used by technicians to assist preclinical diagnosis. The classification of MR images of normal and pathological brains poses a challenge from the technological point of view, since MR imaging generates a large information set that reflects the conditions of the brain. In this paper, we present a computer‐assisted diagnosis method based on wavelet entropy (WE) of the feature space approach and a feed‐forward neural network (FNN) classification method for improving the brain diagnosis accuracy by means of MR images. The most relevant image feature is selected as the WE, which is used to train an FNN classifier. The results using tenfold cross validation of 64 images show that the average accuracy attainable is 100.00%. It can be easily seen from the data that the proposed classifier can detect abnormal brains from normal controls with excellent performance, which can compete with the latest methods. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.